2009
DOI: 10.1002/jnr.22218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the flavonoid casticin from Brazilian Croton betulaster in cerebral cortical progenitors in vitro: Direct and indirect action through astrocytes

Abstract: Neurodegenerative diseases are a major constraint on the social and economic development of many countries. Evidence has suggested that phytochemicals have an impact on brain pathology; however, both their mechanisms of action and their cell targets are incompletely known. Here, we investigated the effects of the flavonoid casticin, extracted from Croton betulaster, a common plant in the state of Bahia in Brazil, on rat cerebral cortex neurons in vitro. Treatment of neural progenitors with 10 microM casticin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…This biflavonoid did not change proliferation or neural differentiation rates in those cells, but it was able to reduce cell death, which was about 35% in 0.1% of DMSO (vehicle) group. The reduction of cell death by FAB is consistent with previous results that show that flavonoids can reduce cell death [10,20]. The exact mechanism by which flavonoids protect against cell death may be vast, as those compounds are widely known not only as antioxidant, but also as activators of PI3 kinase, tyrosine kinase and MAP kinase pathway [4,31,32], enhancers of proteasome activity [33], and modulators of protein assembly and oligomerization [11].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This biflavonoid did not change proliferation or neural differentiation rates in those cells, but it was able to reduce cell death, which was about 35% in 0.1% of DMSO (vehicle) group. The reduction of cell death by FAB is consistent with previous results that show that flavonoids can reduce cell death [10,20]. The exact mechanism by which flavonoids protect against cell death may be vast, as those compounds are widely known not only as antioxidant, but also as activators of PI3 kinase, tyrosine kinase and MAP kinase pathway [4,31,32], enhancers of proteasome activity [33], and modulators of protein assembly and oligomerization [11].…”
Section: Discussionsupporting
confidence: 87%
“…The exact mechanism by which flavonoids protect against cell death may be vast, as those compounds are widely known not only as antioxidant, but also as activators of PI3 kinase, tyrosine kinase and MAP kinase pathway [4,31,32], enhancers of proteasome activity [33], and modulators of protein assembly and oligomerization [11]. Since DMSO is the solvent most suitable for maintaining the stability of RA and FAB [5,6,9,20,23,28], side effects induced by the vehicle might be an inevitable feature of the protocol. In this context, the association of FAB to the protocol becomes applicable in order to reduce inevitably cell death induced by the DMSO and RA.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The high responsiveness of astrocytes to several flavonoids supports the hypothesis that these cells might be mediators of flavonoid actions in the mature brain. Recently, it has been shown that resveratrol counteracts oxidative damage caused by H 2 O 2 , not only by its antioxidant properties, but also through the modulation of important glial functions, particularly improving glutamate uptake activity, increasing glutathione content and stimulating S100b secretion, thus contributing to functional recovery after brain injury [106,107]. Recently, our group investigated the neuroprotective properties of the flavonoid casticin, extracted from Croton betulaster, a common plant of the state of Bahia in Brazil, on rat cerebral cortex neurons in vitro.…”
Section: Role Of Astrocytes As Mediators Of Flavonoid Effectsmentioning
confidence: 99%
“…As shown in Figure 1, accumulated data indicate that casticin was isolated from many plant species such as, namely Vitex agnus castus (Choudhary et al, 2009;Mesaik et al, 2009;Webster et al, 2011;Righeschi et al, 2012;Hogner et al, 2013), Daphne genkwa (Xie et al, 2011), Achillea millefolium (Haidara et al, 2006;Csupor-Loffler et al, 2009), Ficus microcarpa , Vitex rotundifolia (Ono et al, 2002;Hu et al, 2007b;Shen et al, 2009;Ye et al, 2010;Koh et al, 2011), Fructus viticis (Hu et al, 2007b;Guan et al, 2010;Chen et al, 2011b;Yang et al, 2011;Zeng et al, 2012;Zhou et al, 2013a), Vitex negundo (Diaz et al, 2003;Kunwar et al, 2010;Velpandian et al, 2013), Crataegus pinnatifida (Kao et al, 2005), Pavetta crassipes (Mali and Dhake, 2011), Nelsonia canescens, Butea frondosa Koen , Dalbergia odorifera (Mali and Dhake, 2011), Bryonia laciniosa (Aggarwal et al, 2011), Citrus unshu (Mali and Dhake, 2011;Nagoor et al, 2011), Centipeda minima (Mali and Dhake, 2011), Clausena excavate (Manosroi et al, 2005), Croton betulaster (de Sampaio e Spohr et al, 2010;Freitas et al, 2011), Dimorphandra mollis (Freitas et al, 2011), Artemisia abrotanum L. (Hernandez et al, 1999), Artemisia annua L …”
Section: Natural Sources Of Casticinmentioning
confidence: 99%